Upregulation of antioxidant enzymes by organic mineral co-factors to improve oxidative stability and quality attributes of muscle from laying hens. (November 2019) - Liu, Bing; Jiang, Jiang; Lin, Gang; Yu, Dongyou; Xiong, Youling L.
Abstract: This study investigated the impact of organic trace minerals (OTM: Fe, Cu, Mn, and Zn proteinates premix) and Se-yeast (0.25 mg/kg) as a feed supplement versus inorganic forms of the same minerals (sulfated) on the enzymatic (GPX, CAT, SOD), oxidative, and physicochemical properties of fresh breast muscle from 68-week old hens during storage (4 °C) for 0, 2, 4 and 6 days. OTM with Se-yeast was more effective than sulfated minerals or selenite for enriching meat with Zn, Se and vitamin E ( P < .05). At only one-third of the full inorganic mineral supplementation level, OTM with Se-yeast still induced higher GPX activity and greater inhibition of lipid (58% less TBARS) and protein (24% less sulfhydryl loss) oxidation. The organic mineral treatments significantly decreased drip loss and improved color stability of meat when compared with inorganic mineral supplements. Enhanced muscle cellular antioxidant enzymatic activity by the mineral co-factors was plausibly implicated in the protection. Graphical abstract: Unlabelled Image Highlights: The effect of organic trace minerals on hen meat oxidative stability is investigated. Diets with Se-yeast supplementation incorporate more Se and n-3 PUFA in hen meat. Meat from hens fed organic minerals has improved color stability and less drip loss. Organic mineral supplements enhance lipid and protein oxidative stability. Organic minerals boost muscle antioxidant enzyme activity.